MANAJEMEN PEMBIAYAAN PENDIDIKAN DI MTS AR-ROIS CENDEKIA: STRATEGI, TANTANGAN, DAN KEBERHASILAN DALAM MENCAPAI AKSES PENDIDIKAN BERKUALITAS - Aji Yoga Anindita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to analyze the education financing management at MTs Ar-Rois Cendekia with a focus on sources, challenges, strategies, and performance evaluation. A qualitative research method was employed using data collection techniques including participatory observation, in-depth interviews, and document analysis. Findings indicate that the sources of education financing come from various channels, including government funding, community contributions, and student fees. Challenges faced include resource limitations, fund fluctuations, and parental involvement in education financing. To address these challenges, the school has developed various strategies such as diversification of funding sources, enhanced financial transparency, and participatory decision-making approaches. Financial performance evaluations are conducted periodically to ensure the effectiveness of implemented strategies. The implications of these findings underscore the importance of education financing management in achieving quality education objectives. Recommendations include strengthening collaboration with external stakeholders, fundraising efforts, enhancing financial transparency, conducting performance evaluations, and implementing effective risk management.